RISE: Integrating sustainability with life / Professor Sr Dr Zulkiflee Abdul Latif - Abdul Latif, Zulkiflee (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
The Institute for Biodiversity and Sustainable Development (IBSD) has a pivotal role in leading and steering research agendas in UiTM focusing on biodiversity and sustainable development. It led numerous research in various locations including at UiTM owned research station at Kuala Tahan, Taman Negara, Pahang. This year, the Institute is also spearheading a scientific expedition involving researchers from all over the country to collaborate in targeted areas of research, focusing on 13 research topics with 45 researchers have been identified. The areas of research include flora and fauna, tourism, and community which among others include the Bateq community.